Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.cgd.0c00655
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate Transformation via Anhydrate Pairs

Abstract: Here we present an example of an unusual hydrate−anhydrate transformation process induced by defects. Crystallization of uric acid in the presence of substoichiometric concentrations of 2,4-diaminopyrimidine (24-DAP) additives results in uric acid dihydrate (UAD) prisms with trace amounts of 24-DAP included. Prisms maintained in the growth solution transform to anhydrous uric acid (UA) via a highly unusual mechanism in which pairs of thin UA plates emerge from the center of the UAD prism faces which bisect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
1
2
1
Order By: Relevance
“…The crystallographic data and refinement details are presented in Table S3. It was found that MC crystallizes in the space group P2 1 /c including one UA and two water molecules, which is consistent with previous reports (Parkin & Hope, 1998;Artioli et al, 1997;Thornton et al, 2020;Izatulina et al, 2019). But here we also found the presence of disordered UA molecules in the crystal structure with the chemical occupancy 0.688:0.312, as shown in Fig.…”
Section: Mechanism Of the Core-shell Phase Transitionsupporting
confidence: 93%
See 2 more Smart Citations
“…The crystallographic data and refinement details are presented in Table S3. It was found that MC crystallizes in the space group P2 1 /c including one UA and two water molecules, which is consistent with previous reports (Parkin & Hope, 1998;Artioli et al, 1997;Thornton et al, 2020;Izatulina et al, 2019). But here we also found the presence of disordered UA molecules in the crystal structure with the chemical occupancy 0.688:0.312, as shown in Fig.…”
Section: Mechanism Of the Core-shell Phase Transitionsupporting
confidence: 93%
“…The metastable phase UAD can spontaneously transform to UAA through either solid-state dehydration in air or solvent-mediated phase transformation in aqueous solution (Zellelow et al, 2010a;Presores & Swift, 2014). A recent study by Swift and coworkers suggested that the defects induced by trace amounts of 2,4-diaminopyrimidine may impact the kinetics of the solid-state dehydration transition from UAD to UAA (Thornton et al, 2020). However, the unique core-shell phase transition reported in this work was not observed in any of these investigations.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…S1†), stronger characteristic peaks (590, 630, 1012, 1062 cm −1 ) of MSUM appear close to those of UAA and UAD at 550–630 cm −1 and 1000–1065 cm −1 , respectively. In addition, the Raman spectra between UAD and UAA appear quite similar and the discernible differences are at 1431–1640 cm −1 and 1404–1650 cm −1 corresponding to UAD and UAA, 41 respectively (Fig. 2b).…”
Section: Resultsmentioning
confidence: 87%